(untitled) (International Association of Biologicals and Computational Digest, 2022)
Cigarette smoke is a major risk factor in the development of Non-small cell lung cancer (NSCLC). Nicotine- derived nitrosamine ketone (NNK) is an important carcinogen present in cigarette smoke that induces tumor metastasis by activation of a protein kinase cascade, including Focal adhesion kinase (FAK). The present investigation was aimed at employing molecular docking studies to establish binding interactions and comparison of phytocomponents from different herbs and selected Rosmarinic acid derivatives against the target protein FAK with the purpose of blocking the binding of Nicotine-derived nitrosamine ketone (NNK). Molegro virtual docker (MMV) and Hex (version 8.0.0) software was used as docking tool for investigating the interaction of the protein active site residues with the phytocomponents. Molegro molecular viewer (MMV) and Biovia Discovery studio 2017 R2 visualizer were used to identify the amino acid interactions between phytocomponents and protein and also to calculate binding scores. The molecular interaction of NNK with the target protein was also done to obtain the binding energy of this carcinogen with the protein. Rosmarinic acid derivatives manifested the highest docking score with the target protein FAK. In comparison, NNK showed weaker binding score with FAK. In addition the derivatives showed common interacting amino acids. Hence, docking studies indicated that phytocomponents and certain derivatives could effectively bind to the same active site of FAK and block its interaction with NNK. Thus, in nicotine exposed NSCLC patients, Rosmarinic acid derivatives may work as effective competitive binders.